Aplikasi Pembelajaran Pengenalan Budaya Indonesia - Indra Wahyudi; Syamsul Bahri; Popon Handayani (JURNAL TEKNIK KOMPUTER, 2019)
Indonesia is an archipelagic country that has a great diversity of tribes, arts and cultures. The word art and culture are two things that are interrelated and cannot be separated, because each art must have a distinctive culture. But most of us don't know that. Therefore we need to cultivate a sense of nationalism and love for the homeland from an early age, especially children of primary school age. Most schools only use book media to study it so that students get bored quickly, there are many ways that should be done by teachers, one of which is to use headphone media, or commonly called interactive multimedia. The development of interactive media which is part of the information delivery media which is currently a new alternative method that can be used as a means of delivering information in a form that is fun, interesting, easy to understand, and clear, multimedia that is generally known is a variety of graphic combinations, text , sound, video, and animation. This active multimedia learning model is very effective because of the many elements of animation. by utilizing this interactive animation application introducing Indonesian arts and culture created as a solution so students are interested and not easily bored while studying, besides it also makes it easier for students to know and know Indonesian art and culture that are very diverse. This can also make students more love and proud of the culture that Indonesia has. Keywords: Aplication,Multimedia, Culture